Das Lateinische als pro-drop-Sprache: Der Gebrauch von Subjektpronomina in der römischen Komödie aus sprachtypologischer und empirischer Sicht - Lücht, Wilko (Glotta (Göttingen), 2011)
Latin as a pro-drop language shows three variables for the designation of the subject: subject blank, nominal subject and pronominal subject, whereby for this investigation the opposition subject blank - pronominal subject is considered. The use of the subject pronoun in Latin is tied to the basic functions of formal grammatical necessity, disambiguation, focus and intonation. Instead of a strict separation of these areas of use, however, a connection between sentence semantic and formal grammatical reasons can be found in connection with the setting of a subject pronoun. The opposition subject pronoun - subject blank is thus functionalized. Differences in the frequency of the setting of the subject pronoun can be explained by the different frequency of occurrence of the functions that cause the setting of a subject pronoun.